Nursing Markedly Protects Postpartum Mice From Stroke: Associated Central and Peripheral Neuroimmune Changes and a Role for Oxytocin - Stary, Creed M.; Xu, Lijun; Voloboueva, Ludmilla A.; Alcántara-Hernández, Marcela; Arvola, Oiva J.; Idoyaga, Juliana; Giffard, Rona G. (Frontiers in Neuroscience, 2019)
Recent studies demonstrate significant neuroimmune changes in post-partum females, a period that also carries an increased risk of stroke. Oxytocin, a major hormone upregulated in the brains of nursing mothers, has been shown to both modulate neuroinflammation and protect against stroke. In the present study we assessed whether and how nursing modulates the neuroimmune response and injury after stroke. We observed that post-partum nursing mice were markedly protected from 1 hr of transient middle cerebral artery occlusion (MCAO) relative to either non-pregnant/non-postpartum or non-nursing (pups removed) post-partum females. Nursing mice also expressed reduced levels of pro-inflammatory cytokines, had decreased migration of blood leukocytes into the brain following MCAO, and displayed peripheral neuroimmune changes characterized by increased spleen weight and increased fraction of spleen monocytes. Intranasal oxytocin treatment in non-pregnant females in part recapitulated the protective and anti-inflammatory effects associated with nursing. In summary, the results of the present study demonstrate that nursing in the post-partum period provides relative protection against transient ischemic stroke associated with decreased brain leukocytes and increased splenic monocytes. These effects appear to be regulated, at least in part, by oxytocin.